PERANAN SEKTOR PERTANIAN DALAM PERENCANAAN PEMBANGUNAN EKONOMI DI KECAMATAN GALANG KABUPATEN TOLITOLI - Ramlawati, Ramlawati (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2020)
One of the optimization of resources to support the development of the district area can be done by identifying agricultural commodities so that the development strategy of the district area in Tolitoli Regency in the agriculture sector, it can be directed at the priority of developing basic agricultural commodities that can increase growth and balance in the sub-district area. Determination of priority development of agricultural commodities. The aim of the research is to facilitate the local government in planning and making development policies in the sub-district in Tolitoli Regency so that they will be able to maintain and enhance the role of the agricultural sector in the regional economy. The results of the calculation of the average total income obtained by rice farmers per production period (4 months) Rp.2,974,062.13 per hectare, then the amount of rice farmers' income every month is Rp.743,515.53, this shows that the level of income of rice farmers in Galang District, Tolitoli Regency above is not feasible based on the provincial minimum wage (UMP) in Tolitoli Regency. Thus the hypothesis proposed can be accepted. Thus the hypothesis proposed can be accepted. The results of the calculation of economic profitability or return assed (ROA) are an average of 75.80% for each hectare once harvested, then the ability of paddy farmers in Galang District, Tolitoli District to get the benefits of farming through all the available capabilities and resources, shows a very good condition so that the results of farming can be feasible in accordance with the wishes of the farmers. To the paddy rice farmers in Galang District Tolitoli Regency to keep paying attention to the use of poroduction capital, is it in accordance with what is expected or not because the use of the less directed will reduce the efficiency to get maximum benefit. Continuous guidance is needed from relevant agencies to provide guidance to farmers.